High-wear-resistance oil seal material and preparation method thereof
By using acrylate rubber and other specific components in oil sealing materials, the problem of insufficient wear resistance of oil sealing materials is solved, significantly improving the wear resistance and service life of the material, ensuring the safety of mechanical equipment.
Patent Information
- Application Number
- CN202510265297.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-07
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-03-07
AI Technical Summary
The wear resistance of existing oil seal materials is poor, resulting in a short service life and affecting the safety and reliability of mechanical equipment.
Acrylate rubber is used as the base material, combined with components such as polyurethane, polyphthalamide, aluminum borate whiskers and acetylacetone metal complexes, and the wear resistance of the oil sealing material is improved through reasonable proportioning and process treatment.
It significantly improves the wear resistance and service life of oil seal materials, ensuring the safety and reliability of mechanical equipment.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil seal materials, and in particular to a highly wear-resistant oil seal material and a preparation method thereof. Background Art
[0002] Oil seals are usually used as sealing elements in key parts of mechanical equipment, such as steering gears and bearings, to prevent leakage of working media (such as lubricating oil, fuel, etc.) and prevent the intrusion of external dust and impurities. Steering gears, bearings and other parts are key parts for safe driving of automobiles. During operation, they will wear out. When the oil seal material in the parts is damaged, it is easy to cause safety problems, which not only affects the safe driving of the vehicle, but also threatens the life and property safety of the users. Therefore, the wear resistance of oil seal materials is an issue that needs to be paid attention to during the manufacturing and use of oil seal materials.
[0003] Oil seal materials mainly include rubber, plastic and composite materials. Traditional oil seal materials often use rubber materials, mainly nitrile rubber, hydrogenated nitrile rubber, fluororubber, etc. Among them, the cost of nitrile rubber is relatively low, but its sealing performance is limited. The sealing performance of fluororubber is relatively good, but its wear resistance is poor and its service life is relatively short. At present, in order to improve the wear resistance of oil seal materials, inorganic fillers such as SiO2 are usually introduced while selecting base materials with good wear resistance to assist in improving the overall wear resistance and other properties of oil seal materials. However, inorganic fillers usually exist in the interface bonding force of other components is poor and the dispersion is uneven, which has certain limitations on improving the wear resistance of oil seal materials.
[0004] Therefore, it is necessary to develop an oil seal material with good wear resistance, which is of great significance for meeting the oil seal requirements of various parts and extending the service life of the oil seal material. Summary of the invention
[0005] The present invention provides a highly wear-resistant oil seal material and a preparation method thereof, which solves the problem of poor wear resistance of the oil seal material in the related art.
[0006] The technical solution of the present invention is as follows: The present invention provides a highly wear-resistant oil seal material, comprising the following components in parts by weight: 120 parts of acrylic rubber, 15-25 parts of polyurethane, 8-16 parts of polyphthalamide, 16-35 parts of wear-resistant material, 10-15 parts of reinforcing agent, 1-2 parts of vulcanization accelerator, 2-4 parts of vulcanizing agent; The wear-resistant material comprises aluminum borate whiskers and acetylacetone metal complex in a weight ratio of 1 to 9:1.
[0007] As a further technical solution, the weight ratio of the aluminum borate whiskers to the acetylacetone metal complex is 2-6:1.
[0008] When the weight ratio of aluminum borate whiskers to acetylacetone metal complex is 2-6:1, the wear resistance of the oil seal material can be further improved.
[0009] As a further technical solution, the aluminum borate whisker is an aluminum borate whisker composite, and the raw materials of the aluminum borate whisker composite are 4,4'-oxydiphthalic anhydride and aluminum borate whisker.
[0010] In the present invention, 4,4'-oxydiphthalic anhydride is used to compound aluminum borate whiskers, which can improve the bonding strength and compatibility of the aluminum borate whiskers with the acrylic rubber base material, so that when the oil seal material is subjected to external force, the aluminum borate whiskers are not easily pulled out of the matrix, thereby improving the uniformity and density of the oil seal material, thereby improving the tensile strength of the oil seal material.
[0011] As a further technical solution, the weight ratio of the aluminum borate whiskers to the 4,4'-oxydiphthalic anhydride is 20:2-3.
[0012] When the weight ratio of aluminum borate whiskers to 4,4'-oxydiphthalic anhydride is 20:2-3, the tensile strength of the oil seal material can be further improved.
[0013] As a further technical solution, the acetylacetonate metal complex is one or both of acetylacetonate aluminum and acetylacetonate titanium.
[0014] As a further technical solution, the aluminum borate whisker has a length of 15-60 μm and a diameter of 0.3-2.0 μm.
[0015] As a further technical solution, the vulcanization accelerator is one or more of accelerator TMTD, accelerator CBS, and accelerator TETD; The vulcanizing agent is one or more of sulfur, benzoyl peroxide, and dicumyl peroxide; The reinforcing agent is one or both of carbon black and white carbon black.
[0016] As a further technical solution, it also includes at least one of the following features: an antioxidant and a lubricant.
[0017] In the present invention, when the high wear-resistant oil seal material also includes an antioxidant, the added amount of the antioxidant can be 1 to 3 parts by weight. The addition of the antioxidant can ensure the antioxidant ability of the oil seal material to ensure the stability of the oil seal material. The antioxidant can be antioxidant 1010, antioxidant 1076, antioxidant 168, or antioxidant 264.
[0018] In the present invention, when the high wear-resistant oil seal material also includes a lubricant, the amount of the lubricant added can be 1 to 3 parts by weight. The lubricant can form a lubricating film on the contact surface between the oil seal and the shaft, which can reduce friction energy loss while maintaining a good sealing state of the oil seal. The lubricant can be molybdenum disulfide or graphite.
[0019] The present invention also proposes a method for preparing the highly wear-resistant oil seal material, comprising the following steps: S1, mixing the aluminum borate whisker and the acetylacetone metal complex, grinding, and obtaining a wear-resistant material; S2, after the acrylic rubber is plasticized, the remaining components except the vulcanizing agent are added and kneaded, the vulcanizing agent is added and the kneading is continued, and the vulcanization is performed to obtain the oil seal material.
[0020] As a further technical solution, in step S2, after the mixing, it also includes thinning and sheeting to obtain a film.
[0021] As a further technical solution, in step S1, during the mixing, the mixture is first mixed at a stirring speed of 100 to 300 r / min for 1 to 1.5 h, and then mixed at a stirring speed of 700 to 900 r / min for 0.5 to 1 h.
[0022] As a further technical solution, in step S1, during the grinding, the grinding speed is 200-400 r / min, and the grinding time is 40-60 min.
[0023] As a further technical solution, the vulcanization is divided into primary vulcanization and secondary vulcanization. During the primary vulcanization, the vulcanization temperature is 163-168°C and the time is 15-25 minutes; during the secondary vulcanization, the vulcanization temperature is 170-175°C and the time is 45-65 minutes.
[0024] As a further technical solution, the preparation method of the aluminum borate whisker composite comprises the following steps: adding the aluminum borate whisker to water, adjusting the pH to 8.5-9.5, stirring once, separating, and obtaining pretreated aluminum borate whiskers; dispersing the pretreated aluminum borate whiskers and the 4,4'-oxydiphthalic anhydride in ethanol, stirring a second time, separating, and drying, and obtaining the aluminum borate whisker composite.
[0025] As a further technical solution, when adjusting the pH to 8.5-9.5, sodium hydroxide solution or potassium hydroxide solution is used.
[0026] As a further technical solution, during the first stirring, the stirring temperature is 60-70°C, and the stirring time is 0.5-1.5h; during the second stirring, the stirring temperature is 30-38°C, and the stirring time is 2.5-3.5h.
[0027] The working principle and beneficial effects of the present invention are: 1. In the present invention, the oil seal material uses acrylate rubber as the base material, and the acrylate rubber base material can give the oil seal material basic heat oil resistance, so that when the oil seal material contacts lubricating oil and fuel oil with relatively high temperature, the oil seal material can maintain basic stability, making it less likely to deform and other problems. Combined with polyurethane, polyphthalamide, composite wear-resistant material, carbon black, vulcanization accelerator and vulcanizing agent raw material, through the reasonable ratio and synergistic effect of each component, while ensuring the sealing performance of the oil seal material, the wear resistance of the oil seal material can also be improved, thereby increasing the service life of the oil seal material.
[0028] 2. The composite wear-resistant material includes aluminum borate whiskers and acetylacetone metal complexes. The acetylacetone metal complexes can make the rubber base material and other components interact more closely, and can also improve the interfacial bonding strength between the aluminum borate whiskers and the base material. The combined use of aluminum borate whiskers and acetylacetone metal complexes can support the oil seal material, disperse the friction stress of the oil seal material to a certain extent, and reduce the wear of the oil seal material. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In the following examples and comparative examples, the model of the acrylic rubber is AR-140; the model of the polyurethane is TPUS98A; the model of the polyphthalamide is GVS-5H; and the average length of the aluminum borate whisker is 20 μm and the diameter is 1.0 μm.
[0031] Example 1 A highly wear-resistant oil seal material comprises the following components in parts by weight: 120 parts of acrylic rubber, 15 parts of polyurethane, 8 parts of polyphthalamide, 2 parts of molybdenum disulfide, 2 parts of antioxidant 1010, 16 parts of wear-resistant materials, 10 parts of carbon black, 1 part of accelerator TMTD, 2 parts of diisopropylbenzene peroxide; The composite wear-resistant material includes 8 parts of aluminum borate whiskers and 8 parts of titanium acetylacetonate; A method for preparing a highly wear-resistant oil seal material comprises the following steps: S1, mixing aluminum borate whiskers and titanium acetylacetonate at a stirring speed of 100 r / min for 1.5 h, then mixing at a stirring speed of 700 r / min for 1 h, and then grinding at 200 r / min for 60 min to obtain a wear-resistant material; S2, after the acrylic rubber is plasticized, the remaining components except dicumyl peroxide are added and mixed, and the mixing is continued after the dicumyl peroxide is added, and the mixture is thinned 5 times and filmed to obtain a film; S3. After the film is left standing for 24 hours, it is vulcanized at 163° C. for 25 minutes, and then at 170° C. for 65 minutes to obtain an oil seal material.
[0032] Example 2 A highly wear-resistant oil seal material comprises the following components in parts by weight: 120 parts of acrylic rubber, 20 parts of polyurethane, 12 parts of polyphthalamide, 21 parts of wear-resistant material, 12 parts of white carbon black, 1.5 parts of accelerator CBS, 3 parts of benzoyl peroxide; The composite wear-resistant material includes 12 parts of aluminum borate whiskers and 9 parts of aluminum acetylacetonate; A method for preparing a highly wear-resistant oil seal material comprises the following steps: S1, mixing aluminum borate whiskers and aluminum acetylacetonate at a stirring speed of 200 r / min for 1 h, then mixing at a stirring speed of 800 r / min for 0.5 h, and then grinding at 300 r / min for 50 min to obtain a wear-resistant material; S2, after the acrylic rubber is plasticized, the remaining components except benzoyl peroxide are added and mixed, and the mixing is continued after the benzoyl peroxide is added, and the mixture is thinned 5 times and filmed to obtain a film; S3. After the film is left standing for 24 hours, it is vulcanized at 166° C. for 20 minutes, and then at 175° C. for 55 minutes to obtain an oil seal material.
[0033] Example 3 A highly wear-resistant oil seal material comprises the following components in parts by weight: 120 parts of acrylic rubber, 25 parts of polyurethane, 16 parts of polyphthalamide, 2 parts of molybdenum disulfide, 35 parts of wear-resistant materials, 15 parts of carbon black, 2 parts of accelerator TETD, 4 parts of sulfur; The composite wear-resistant material includes 31.5 parts of aluminum borate whiskers and 3.5 parts of aluminum acetylacetonate; A method for preparing a highly wear-resistant oil seal material comprises the following steps: S1, mixing aluminum borate whiskers and aluminum acetylacetonate at a stirring speed of 300 r / min for 1 h, then mixing at a stirring speed of 900 r / min for 0.5 h, and then grinding at 400 r / min for 40 min to obtain a wear-resistant material; S2, after the acrylic rubber is plasticized, the remaining components except sulfur are added and mixed, and the mixing is continued after the sulfur is added, and the mixture is thinned 5 times and filmed to obtain a film; S3. After the film is left standing for 24 hours, it is vulcanized at 168° C. for 15 minutes, and then at 175° C. for 45 minutes to obtain an oil seal material.
[0034] Example 4 The only difference between this embodiment and embodiment 2 is that, in this embodiment, the wear-resistant material includes 20 parts of aluminum borate whiskers and 1 part of aluminum acetylacetonate.
[0035] Example 5 The only difference between this embodiment and embodiment 2 is that in this embodiment, the wear-resistant material includes 14 parts of aluminum borate whiskers and 7 parts of aluminum acetylacetonate.
[0036] Example 6 The only difference between this embodiment and embodiment 2 is that in this embodiment, the wear-resistant material includes 18 parts of aluminum borate whiskers and 3 parts of aluminum acetylacetonate.
[0037] Example 7 The difference between this embodiment and embodiment 6 is that, in this embodiment, the aluminum borate whisker is an aluminum borate whisker composite; The preparation method of the highly wear-resistant oil seal material comprises the following steps: S0, adding 20 parts of aluminum borate whiskers to 100 parts of water, adjusting the pH to 9 with a 10% by weight sodium hydroxide solution, stirring at 65° C. for 1 hour, separating to obtain pretreated aluminum borate whiskers, dispersing the pretreated aluminum borate whiskers and 1 part of 4,4'-oxydiphthalic anhydride in 100 parts of ethanol, stirring at 35° C. for 3 hours, separating, and drying to obtain an aluminum borate whisker composite; S1, 18 parts of the aluminum borate whisker composite and 3 parts of aluminum acetylacetonate were mixed at a stirring speed of 200 r / min for 1 hour, then at a stirring speed of 800 r / min for 0.5 hour, and then ground at 300 r / min for 50 minutes to obtain a wear-resistant material; S2, after the acrylic rubber is plasticized, the remaining components except benzoyl peroxide are added and mixed, and the mixing is continued after the benzoyl peroxide is added, and the mixture is thinned 5 times and filmed to obtain a film; S3. After the film is left standing for 24 hours, it is vulcanized at 166° C. for 20 minutes, and then at 175° C. for 55 minutes to obtain an oil seal material.
[0038] Example 8 The only difference between this embodiment and embodiment 7 is that in the preparation process of the aluminum borate whisker composite in this embodiment, 4 parts of 4,4'-oxydiphthalic anhydride are added.
[0039] Example 9 The only difference between this embodiment and embodiment 7 is that, in the preparation process of the aluminum borate whisker composite in this embodiment, 2 parts of 4,4'-oxydiphthalic anhydride are added.
[0040] Example 10 The only difference between this embodiment and embodiment 7 is that, in the preparation process of the aluminum borate whisker composite in this embodiment, 3 parts of 4,4'-oxydiphthalic anhydride are added.
[0041] Comparative Example 1 The difference between this comparative example and Example 1 is that in this comparative example, titanium acetylacetonate is not added, and 16 parts of aluminum borate whiskers are added.
[0042] Comparative Example 2 The only difference between this comparative example and Example 1 is that in this comparative example, the aluminum borate whiskers are replaced with an equal amount of needle-shaped wollastonite.
[0043] Comparative Example 3 The only difference between this comparative example and Example 1 is that in this comparative example, no wear-resistant material is added.
[0044] Comparative Example 4 The difference between this comparative example and Example 1 is that in this comparative example, no aluminum borate whisker is added, and 16 parts of titanium acetylacetonate are added.
[0045] Experimental example: Wear resistance test The oil seal materials prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were subjected to volume wear tests according to the method specified in GB / T 9867-2008 "Determination of wear resistance of vulcanized rubber or thermoplastic rubber (rotating roller abrasion machine method)", wherein the test results are the average values of 3 samples; The test results are shown in Table 1 below: Table 1 Wear resistance test results of Examples 1 to 6 and Comparative Examples 1 to 4
[0046] It can be seen from Table 1 that the volume wear of the oil seal material prepared by this scheme is less than 0.320cm 3 , indicating that the oil seal material prepared by this scheme has good wear resistance. Among them, compared with comparative examples 1 to 4, the volume wear of examples 1 to 3 is significantly reduced, indicating that the wear resistance of the oil seal material can be improved by compounding aluminum borate whiskers and acetylacetone metal complexes. In addition, compared with examples 2 and 4, the volume wear of examples 5 to 6 is significantly reduced, indicating that when the weight ratio of aluminum borate whiskers to acetylacetone metal complexes is 2 to 6:1, the wear resistance of the oil seal material can be further improved.
[0047] Experimental Example 2 Tensile Strength Test The oil seal materials prepared in Examples 6 to 10 were subjected to a tensile strength test according to GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber", wherein the sample type was type 1, the moving speed was 500 mm / min, and the test result was the average value of 3 samples; The test results are shown in Table 2 below: Table 2 Tensile strength test results of Examples 6 to 10
[0048] Compared with Example 6, the tensile strength of the oil seal material prepared in Examples 7 to 10 is improved, indicating that the tensile strength of the oil seal material can be improved by compounding the aluminum borate whisker with 4,4'-oxydiphthalic anhydride. Among them, compared with Examples 7 to 8, the tensile strength of the oil seal material prepared in Examples 9 to 10 is improved, indicating that when the weight ratio of aluminum borate whisker to 4,4'-oxydiphthalic anhydride is 20:2 to 3, the tensile strength of the oil seal material can be further improved.
[0049] Experimental Example 3 The oil seal material prepared in Example 1 was subjected to the following performance tests: ①Hardness: Hardness test shall be carried out according to the method in GB / T 531.1-2008 "Test method for indentation hardness of vulcanized rubber or thermoplastic rubber Part 1: Shore hardness tester method (Shore hardness)"; ②Aging resistance test: Place the sample in a high temperature box at 150℃ for 84h for heat aging experiment, take it out and cool it down, and then conduct tensile strength test after heat aging in accordance with GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber". The sample type is type 1, the moving speed is 500mm / min, and the test result is the average value of 3 samples; The test results are shown in Table 3: Table 3 Performance test results of Example 1
[0050] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A highly wear-resistant oil seal material, characterized in that: The composition comprises the following components in parts by weight: 120 parts of acrylic rubber, 15-25 parts of polyurethane, 8-16 parts of polyphthalamide, 16-35 parts of wear-resistant material, 10-15 parts of reinforcing agent, 1-2 parts of vulcanization accelerator, 2-4 parts of vulcanizing agent; The wear-resistant material comprises aluminum borate whiskers and acetylacetone metal complex in a weight ratio of 1 to 9:
1.
2. A highly wear-resistant oil seal material according to claim 1, characterized in that: The weight ratio of the aluminum borate whisker to the acetylacetone metal complex is 2-6:
1.
3. A highly wear-resistant oil seal material according to claim 1, characterized in that: The aluminum borate whisker is an aluminum borate whisker composite, and the raw materials of the aluminum borate whisker composite are 4,4'-oxydiphthalic anhydride and aluminum borate whisker.
4. A highly wear-resistant oil seal material according to claim 3, characterized in that: The weight ratio of the aluminum borate whisker to the 4,4'-oxydiphthalic anhydride is 20:2-3.
5. A highly wear-resistant oil seal material according to claim 1, characterized in that: The acetylacetonate metal complex is one or both of acetylacetonate aluminum and acetylacetonate titanium.
6. A highly wear-resistant oil seal material according to claim 1, characterized in that: The vulcanization accelerator is one or more of accelerator TMTD, accelerator CBS, and accelerator TETD; The vulcanizing agent is one or more of sulfur, benzoyl peroxide, and dicumyl peroxide; The reinforcing agent is one or both of carbon black and white carbon black.
7. A highly wear-resistant oil seal material according to claim 1, characterized in that: It also includes at least one of the following features: antioxidant, lubricant.
8. The method for preparing a highly wear-resistant oil seal material according to claim 1, characterized in that: The following steps are involved: S1, mixing the aluminum borate whiskers and the acetylacetone metal complex, grinding, and obtaining a wear-resistant material; S2, after the acrylic rubber is plasticized, the remaining components except the vulcanizing agent are added and kneaded, the vulcanizing agent is added and the kneading is continued, and the vulcanization is performed to obtain the oil seal material.
9. The method for preparing a highly wear-resistant oil seal material according to claim 8, characterized in that: In step S1, during the mixing, the mixture is first mixed at a stirring speed of 100 to 300 r / min for 1 to 1.5 h, and then mixed at a stirring speed of 700 to 900 r / min for 0.5 to 1 h.
10. The method for preparing a highly wear-resistant oil seal material according to claim 8, characterized in that: The vulcanization is divided into primary vulcanization and secondary vulcanization. During the primary vulcanization, the vulcanization temperature is 163-168° C. and the time is 15-25 minutes; during the secondary vulcanization, the vulcanization temperature is 170-175° C. and the time is 45-65 minutes.
Citation Information
Patent Citations
Acrylate rubber composite material
CN103224678A
Engine oil seal rubber material and preparation method thereof
CN106519525A
OCA optical glue for bonding mobile phone frame
CN107903828A
Self-lubricating rubber composition and preparation process thereof
CN116874962A
High-wear-resistance low-heat-generation acrylate rubber material for high-speed oil seal and preparation method thereof
CN117511102A
Cited By
Heat insulation coating containing rare earth and preparation method thereof
CN121249219A